Political Violence and Sectarianism in Pakistan - Dorsey, James Michael (2016)
Pakistan’s generals blame their country’s cycle of political violence, including a recent bombing in the Baluch capital of Quetta, on groups in Afghanistan. The focus on external enemies complicates efforts to reduce political violence, ease inter-communal strains, and facilitate easing of tensions with Pakistan’s neighbours.